One piece. Baroque Works. Vol. 14, Instinct - Oda, Eiichiro, 1975-; Caselman, Lance; JN Productions (San Francisco, CA : VIZ Media, LLC, 2007)
Luffy tries to help Dorry the Giant find out who slipped him some exploding ale in the hopes of saving his own neck from the giant's wrath.
"First published by in Japan in 1997 by Shueisha Inc, Tokyo"--Page facing t.p.
"Parental advisory. One Piece is rated T for teen and is recommended for ages 13 and up. This v. contains fantasy violence and tobacco usage"--Page facing t.p.
"This book reads from right to left"--Back cover.
"This v. contains material that was originally published in English in Shonen Jump #48-51"--Page facing t.p.
Translated from the Japanese.
Adult
Keywords: Pirates -- Comic books, strips, etc. -- Fiction; Treasure troves -- Comic books, strips, etc. -- Fiction; Buried treasure -- Comic books, strips, etc. -- Fiction; Manga; Pirates -- Comic books, strips, etc. -- Fiction; Action and adventure comics; Graphic novels